The Study On The Implementation Of Teaching Reading In The Fifth Grade Of SDN 2 Banyuagung Surakarta - Riyanti, Rini May, Dra. Malikatul Laila, M. Hum, Titis Setyabudi, S.S. M. Hum (2014)
This study aims to find out the component of teaching reading and to describe the implementation of teaching reading in the fifth grade of SDN Banyuagung 2 Surakarta. The result of this study is contributed the teaching of learning reading. To find the results, the researcher took the information from the students' answers on written test in the form of pre-test and post-test. Type of the research is descriptive qualitative research. The researcher took the information from observation, interview and document in the teaching and learning of reading. The result of the research showed that after the writer conducted the action, the student's motivation to read, to study reading, and student's achievement of reading has improved. It can be seen from the result of the students' activities during the action, the students' reading achievement of reading in the form of score sheet, and the mean of pre-test and post-test. Drawn from the analysis of the process teaching learning reading using group of student by the descriptive texts and from the assessment, the use of group technique is very suitable or appropriate in teaching learning of reading process to know the implementation of teaching reading in the fifth grade of SDN Banyuagung 2 Surakarta Meanwhile, to find the significant difference between students' achievement before and after action, the writer used pre-test and post-test. The students could do the post-test better than pre-test, meaning that the teaching reading using group action in the class is successful to improve students' motivation to read, to study reading, and to improve students' reading achievement.